Where Is More Important Than How in Coastal and Marine Ecosystems Restoration - Fraschetti, Simonetta; McOwen, Chris; Papa, Loredana; Papadopoulou, Nadia; Bilan, Meri; Boström, Christoffer; Capdevila, Pol; Carreiro-Silva, Marina; Carugati, Laura; Cebrian, Emma; Coll, Marta; Dailianis, Thanos; et al. (Frontiers in Marine Science, 2021)
Restoration is considered an effective strategy to accelerate the recovery of biological communities at local scale. However, the effects of restoration actions in the marine ecosystems are still unpredictable. We performed a global analysis of published literature to identify the factors increasing the probability of restoration success in coastal and marine systems. Our results confirm that the majority of active restoration initiatives are still concentrated in the northern hemisphere and that most of information gathered from restoration efforts derives from a relatively small subset of species. The analysis also indicates that many studies are still experimental in nature, covering small spatial and temporal scales. Despite the limits of assessing restoration effectiveness in absence of a standardized definition of success, the context (degree of human impact, ecosystem type, habitat) of where the restoration activity is undertaken is of greater relevance to a successful outcome than how (method) the restoration is carried out. Contrary to expectations, we found that restoration is not necessarily more successful closer to protected areas (PA) and in areas of moderate human impact. This result can be motivated by the limits in assessing the success of interventions and by the tendency of selecting areas in more obvious need of restoration, where the potential of actively restoring a degraded site is more evident. Restoration sites prioritization considering human uses and conservation status present in the region is of vital importance to obtain the intended outcomes and galvanize further actions.